The Relevance of Immanuel Kant's Enlightenment Philosophy in Human Capital Development - Choirul Anam (Optima Science, 2024)
This study explores the application of Immanuel Kant's Enlightenment philosophy to the development of human capital. The focus is to explore the contribution of concepts such as autonomy, rationality, and freedom of thought to the enhancement of individual capacity and value in organizations. This research uses a qualitative approach with literature analysis and case study methods. Data were collected from various academic and practical sources related to human capital development and Kant's philosophy. The analysis was conducted interpretatively to identify and relate Kantian concepts to human capital management practices. The application of Kantian principles in human capital development encourages employees to think critically, innovate, and act independently. Academic and professional freedom supported by the organization allows individuals to develop their potential to the fullest, which in turn improves organizational performance and creativity. Immanuel Kant's Enlightenment principles have strong relevance in the context of human capital development. Individual autonomy, the use of rationality, and the courage to think freely are key elements that can strengthen and enhance human capital capacity in postmodern organizations. The findings can serve as a basis for human capital development strategies that focus more on individual empowerment and enhancing critical thinking capacity in modern work environments.